(3JMdjd GdGSJKeGQ aj GdHfhc (B/s - (3Ndhaj, hgjHIs ((3YeGf(B: s (3OGQ GdGYUGQ GdYdej ddfTQ hGdJhRjY(B, s, 2017)
(3GdJMdjd GdQCSj GdYehOj dbGFeI GdONd,eaghe eNGWQ GdGSJKeGQ,WHjYI eNGWQ GdGSJKeGQ aj GdeUGQa GdESdGejI,eNGWQ eUOQgG fhYjI GdehGQO GdHTQjI GdeJGMI,eYGjjQ Jbhje hSGFd GdGSJKeGQ aj GdHfhc GdGSdGejI,eaghe GdHfc GdJLGQj,hXGFa hCfTWI GdHfc GdJLGQj,GdeMaXI GdGSJKeGQjI,GdHfhc GdGdcJQhfjIs
(3HjHdjhZQGajG(B: (3U(B.177-179s
Keywords: (3GdGSJKeGQs; (3GdHfhcs